2017
DOI: 10.3390/ma10060631
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Photocatalytic Properties of Mn-Doped TiO2 Loaded on Wood-Based Activated Carbon Fiber Composites

Abstract: Mn-doped TiO2 loaded on wood-based activated carbon fiber (Mn/TiO2-WACF) was prepared by sol–gel and impregnation method using MnSO4·H2O as manganese source. The structure of Mn/TiO2–WACF was characterized by SEM, XRD, FTIR, N2 adsorption and UV–Vis, and its photocatalytic activity for methylene blue degradation was investigated. Results show that Mn-doped TiO2 were loaded on the surface of wood-based activated carbon fiber with high-development pore structures. The crystallite sizes of Mn-doped TiO2 in compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Other carbon-containing functional groups of CC (1636 cm –1 ), CN (1636 cm –1 ), C–N (1177, 1141, and 1083 cm –1 ), CO (1704 cm –1 ), and C–O (1177, 1141, and 1083 cm –1 ) were also observed for the acid-treated CF. In addition, sulfoxide was observed at the 1051 cm –1 (SO) and the NO bonding was found at 1545 cm –1 . There are numerous functional groups attached on the acid-treated CF, whereas nearly no peaks were observed in the FTIR spectrum for the untreated CF. These phenomena greatly suggest the success of the acid treatment to generate numerous functional groups, which can provide extra Faradaic redox reactions to enhance the energy storage ability of CF electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Other carbon-containing functional groups of CC (1636 cm –1 ), CN (1636 cm –1 ), C–N (1177, 1141, and 1083 cm –1 ), CO (1704 cm –1 ), and C–O (1177, 1141, and 1083 cm –1 ) were also observed for the acid-treated CF. In addition, sulfoxide was observed at the 1051 cm –1 (SO) and the NO bonding was found at 1545 cm –1 . There are numerous functional groups attached on the acid-treated CF, whereas nearly no peaks were observed in the FTIR spectrum for the untreated CF. These phenomena greatly suggest the success of the acid treatment to generate numerous functional groups, which can provide extra Faradaic redox reactions to enhance the energy storage ability of CF electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…It can prevent CF substrate from contacting the oxygen directly. The type of coating can be various, such as metal coating (Zn, Ni, Cu, Ti, Zr, Ag); oxides coating (SiO 2 , Fe 3 O 4 , Al 2 O 3 , TiO 2 ), nitrides coating (BN, TiN), carbides coating (SiC, TiC, TaC, ZrC, B 4 C), and composite coating (Al 2 O 3 /Y 2 O 3 , ZrC–ZrB 2 –SiC, SiBNC) [5,6,7,8,9,10,11,12,13,14,15,16]. Among them, ceramic coatings are the most promising coatings due to the fact that they are much lighter and have better wettability, which can reduce interface diffusion and reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the surface area was reduced with Mn doping due to partial pore blockage by Mn, which was consistent with previous work [ 23 ]. In contrast, previous works reported that the surface area increased with the increasing of the Mn concentration [ 35 ]. It should be noted that the surface area of all the Mn-doped samples in the current study was higher than the commercial TiO 2 (50 m 2 /g).…”
Section: Resultsmentioning
confidence: 59%
“…The crystallite sizes of Mn-TiO 2 increased in the current study, consistent with previous work [ 34 ]. In contrast, Ma et al [ 35 ] reported a decrease in the crystallite size of TiO 2 with the increasing of the Mn doping level. The crystallinity decreased from 62.89 to 45.79% upon the increasing of the Mn concentration to 0.5 wt%.…”
Section: Resultsmentioning
confidence: 92%